Gestão democrática: processos educacionais e as práticas gestoras nas escolas municipais de Icó-Ceará - Sousa, Aurineide Amaro (My University, 2024)
This research entitled "Democratic Management: educational processes and management practices in municipal schools in Icó - Ceará" was carried out alongside the Master's in Education course at the University of Caxias do Sul, in the line of research in Educational Processes, Language, Technology and Inclusion , and had the following problem: What is the democratic management model implemented in schools in the Municipal Network of Icó, and how does this model relate to educational processes and the practices of school managers? The general objective was to investigate which educational processes and practices of school managers contribute to the implementation of a democratic management model in the Municipal Network of Icó/CE. During the study it was found that the concept of democratic management is one of the greatest challenges faced by school institutions. To respond to this problem, three specific objectives were proposed: (a) identify how education theorists approach democratic management in public schools; (b) establish educational macro and micro policies that require the use of democratic management in Icó's school institutions; and (c) analyze educational processes and practices based on the speeches of school managers to point out the relationships with the manager's functions from a democratic perspective. Considering the investigative perspective of this study, the theoretical support included Paro (2002), Veiga (1997), Hora (2002), Sacristán (2001) and Cury (2008), in the discussion on the concept of democratic management. Within the scope of the discussion of macro and micro policies in school management, there is an analysis of documentation such as Law No. 9,394/96 on Guidelines and Bases of Brazilian Education associated with the studies by Thomazini (2020) and Silva (2021). Regarding the concepts of autonomy within the practices of school managers, authors Gadotti (1990), Bacilar (1997), Freire (1983, 2010), Martins (2010) and Libâneo (2004, 20012) contribute. Furthermore, in the discussion of educational processes managed by educational managers in a democratic way, dialogues are established with Sousa (2015, 2019), Vasconcelos (2018), Passos (2018), Vicin (2002), Luck (2000) and Drucker. (1992). In relation to the qualitative approach (BOGDAN; BIKLEN, 1994) and located in the field of research in education, the research methodology was inspired by the Case Study approach (YIN, 1986). The data constructed was based on the study of the concept of democratic management; on-site observation of the school units studied; the analysis of documents such as: the Pedagogical Political Project and the School Regulations; and the use of semi-structured questionnaires with open and multiple-choice questions that were answered by managers from two schools participating in the research. The results obtained point to a democratic management profile aligned with the theoretical concepts that supported this research, as well as the existence of these concepts in the documents analyzed. However, it is clear that educational processes are still moving slowly towards implementation in managers' practices. The analysis of the managers' discourse points to the importance of democratization mechanisms, especially for the necessary and effective participation of the school community in the implementation of Macro and Micro public policies. To this end, it is suggested that the Municipal Education Network of Icó-CE improve the use of management practices that favor the autonomy of spaces and the implementation of participatory decisions in educational processes and in the democratic management of schools in the Municipal Education Network. [resumo fornecido pelo autor]
A presente pesquisa intitulada "Gestão Democrática: processos educacionais e práticas gestoras nas escolas municipais de Icó - Ceará" foi realizada junto ao curso de Mestrado em Educação da Universidade de Caxias do Sul, na linha de pesquisa em Processos Educacionais, Linguagem, Tecnologia e Inclusão, e teve como problemática: Qual o modelo de gestão democrática implantado nas escolas da Rede Municipal de Icó, e como este modelo se relaciona com os processos educacionais e as práticas dos gestores escolares? O objetivo geral consistiu em investigar quais são os processos educacionais e as práticas dos gestores escolares que contribuem para a efetivação de um modelo de gestão democrática na Rede Municipal de Icó/CE. Durante o estudo constatou-se que o conceito de gestão democrática é um dos grandes desafios enfrentados pelas instituições escolares. Para responder essa problemática, foram propostos três objetivos específicos: (a) identificar como os teóricos da educação abordam a gestão democrática nas escolas públicas; (b) estabelecer as macro e as micropolíticas educacionais que exigem a utilização da gestão democrática nas instituições escolares de Icó; e (c) analisar os processos educacionais e as práticas a partir das falas dos gestores escolares para apontar as relações com as funções do gestor na perspectiva democrática. Considerando o prisma investigativo deste estudo, o aporte teórico contou-se com Paro (2002), Veiga (1997), Hora (2002), Sacristán (2001) e Cury (2008), na discussão sobre o conceito de gestão democrática. No âmbito da discussão das macro e das micro políticas na gestão escolar, tem-se a análise das documentações como Lei No. 9.394/96 de Diretrizes e Bases da Educação Brasileira associada aos estudos de Thomazini (2020) e Silva (2021). No que tange aos conceitos de autonomia dentro das práticas dos gestores escolares, contribuem os autores Gadotti (1990), Bacilar (1997), Freire (1983, 2010), Martins (2010) e Libâneo (2004, 2012). Ainda, na discussão dos processos educacionais geridos pelos gestores educacionais de forma democrática, são estabelecidos diálogos com Sousa (2015, 2019), Vasconcelos (2018), Passos (2018), Vicin (2002), Luck (2000) e Drucker. (1992). Em relação a abordagem qualitativa (BOGDAN; BIKLEN, 1994) e situada no campo das pesquisas em educação, a metodologia de pesquisa teve inspiração na abordagem do Estudo de Caso (YIN, 1986). Os dados construídos foram a partir do estudo do conceito de gestão democrática; da observação em loco das unidades escolares estudadas; da análise de documentos como: o Projeto Político Pedagógico e os Regimentos Escolares; e da utilização de questionários semiestruturados com questões abertas e de múltipla escolha que foram respondidos por gestores de duas escolas participantes da pesquisa. Os resultados obtidos apontam um perfil de gestão democrática alinhado aos conceitos teóricos que embasaram esta pesquisa, bem como a existência desses conceitos nos documentos analisados. Contudo, percebe-se que os processos educacionais ainda caminham a passos lentos para sua efetivação nas práticas dos gestores. A análise do discurso dos gestores aponta para a menção da importância dos mecanismos de democratização, especialmente para a necessária e efetiva participação da comunidade escolar na implantação das Macro e Micro politicas públicas. Para tanto, sugere-se que a Rede Municipal de Ensino de Icó-CE aprimore a utilização de práticas gestoras que favoreçam a autonomia dos espaços e a efetivação de decisões participativas nos processos educacionais e na gestão democrática das escolas da Rede Municipal de Ensino. [resumo fornecido pelo autor]
Keywords: Escolas - Organização e administração - Icó (CE); Educação; Escolas públicas; Schools - Organization and administration - Icó (Brazil); Education; Public schools